1990
DOI: 10.1159/000186176
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Levels of C-Reactive Protein in Hemodialysis Patients

Abstract: Serum C-reactive protein (CRP) levels were measured by nephelometry in 30 healthy subjects (controls) and in 99 patients with uncomplicated terminal uremia on conservative therapy (group 1, n = 30) or chronic hemodialysis (group 2, n = 69). Whereas there was no difference between controls and group 1, both the mean concentration of CRP and the incidence of elevated levels were significantly higher in group 2 in comparison with both controls and group 1. Moreover, the degree of increase in these patients was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 8 publications
4
36
0
Order By: Relevance
“…Although 29% of hemodialyzed and 56% of uremic patients had elevated CRP levels, there was no correlation with the levels of circulating IL-6. Our observation is in agreement with the recent data reported by Docci et al [30] who showed that mean levels of CRP were elevated in the sera of hemodia lyzed patients. Recently, an increased level of serum amy loid A (SAA) was noticed during the dialysis session [31], Although IL-6 triggers the production of SAA, this ob served enhancement cannot be related to IL-6 since the levels of this cytokine remained unchanged during the dialysis session.…”
Section: Discussionsupporting
confidence: 94%
“…Although 29% of hemodialyzed and 56% of uremic patients had elevated CRP levels, there was no correlation with the levels of circulating IL-6. Our observation is in agreement with the recent data reported by Docci et al [30] who showed that mean levels of CRP were elevated in the sera of hemodia lyzed patients. Recently, an increased level of serum amy loid A (SAA) was noticed during the dialysis session [31], Although IL-6 triggers the production of SAA, this ob served enhancement cannot be related to IL-6 since the levels of this cytokine remained unchanged during the dialysis session.…”
Section: Discussionsupporting
confidence: 94%
“…Inflammation is a highly prevalent condition among CKD patients. Crosssectional studies have shown that 30-50% of nondialysis (Ortega et al, 2002) and dialysis (Docci et al, 1990;McIntyre et al, 1997) patients present serologic evidence of an activated inflammatory response with elevated serum concentration of C-reactive protein (CRP). Our group has recently reported increased REE in nondialysis patients with CRP40.5 mg/dl (Avesani et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…Also, hs-CRP levels correlate with the length of dialysis in ESRD patients alluding to a strong involvement of the protein in the inflammatory process [7]. This is important given recent reports linking altered hs-CRP levels with cardiac hypertrophy and increased arterial stiffness [5, 6, 8].…”
Section: Introductionmentioning
confidence: 99%